2013
DOI: 10.1007/s00401-013-1091-z
|View full text |Cite
|
Sign up to set email alerts
|

Nervous system involvement in von Hippel–Lindau disease: pathology and mechanisms

Abstract: Patients with von Hippel-Lindau disease carry a germline mutation of the Von Hippel-Lindau (VHL) tumor-suppressor gene. We discuss the molecular consequences of loss of VHL gene function and their impact on the nervous system. Dysfunction of the VHL protein causes accumulation and activation of hypoxia inducible factor (HIF) which can be demonstrated in earliest stages of tumorigenesis and is followed by expression of VEGF, erythropoietin, nitric oxide synthase and glucose transporter 1 in VHL-deficient tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 164 publications
2
32
0
2
Order By: Relevance
“…2 Several studies have indicated that VHL deficient hemangioblastoma precursor cells, tumorlets, are established during embryonic development, although the exact tumorigenesis is still unknown. [17][18][19][20][21][22] Thus, from birth, vHL patients may harbor numerous microscopic tumorlets in the CNS, including the retina, and similar growth patterns would be expected. Differing anatomical and diagnostic limitations may account for some of the observed disparity in tumor development at the two sites.…”
Section: Variation In Manifestation Rate Depends On the Anatomical Lomentioning
confidence: 99%
“…2 Several studies have indicated that VHL deficient hemangioblastoma precursor cells, tumorlets, are established during embryonic development, although the exact tumorigenesis is still unknown. [17][18][19][20][21][22] Thus, from birth, vHL patients may harbor numerous microscopic tumorlets in the CNS, including the retina, and similar growth patterns would be expected. Differing anatomical and diagnostic limitations may account for some of the observed disparity in tumor development at the two sites.…”
Section: Variation In Manifestation Rate Depends On the Anatomical Lomentioning
confidence: 99%
“…However, it is known that more than 93% of hemangioblastomas occurs in the posterior fossa of the brain and spinal hemangioblastoma is a rare tumor which occurs mostly in patients with VHL syndrome [29,30]. In our dataset, none of the patients with possible VHL had spinal hemangioblastoma.…”
Section: Discussionmentioning
confidence: 63%
“…These defects can lead to disease manifestations in tissues beyond the kidney, where abnormal vascular growth and remodeling contribute to additional pathologies. For instance, brain, spinal cord, and eye/retina hemangioblastoma formation is commonplace in VHL disease (94,95), owing in part to disruption of the VEGF-A (96, 97) and Notch pathways (98), among others. Dysfunction in HIF signaling is also likely involved in the aberrant vessel remodeling found in nonkidney tissues, as recent studies have implicated this pathway, and downstream mediators such as ANGPT-like 4 (ANGPTL4), in angiogenesis-related conditions including pterygia (99), uveal melanoma (100), and proliferative retinopathies (101)(102)(103).…”
Section: Hlrcc: An Illustration Of Metabolically Driven Hereditary Kimentioning
confidence: 99%
“…Aberrant blood vessel formation also gives rise to hemangioblastomas in the cerebellum and spinal cord of VHL patients (94,113,114). Similarly to the kidney, these tissues have high metabolic Angiogenesis, a theme in hereditary kidney cancer risk Misregulated vascular growth and remodeling contribute to the onset and progression of numerous tumor types (59), and these processes are particularly relevant to hereditary kidney cancers.…”
Section: Hlrcc: An Illustration Of Metabolically Driven Hereditary Kimentioning
confidence: 99%